(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article discusses the main aspects of the substantiation of theoretical and practical approaches to the formulation of works on the development of skills and abilities of self-service in children with a severe degree of mental retardation in a specialized orphanage. Since it is known that their independence in these matters largely depends on the correct organization and implementation of work on the upbringing and training of these children. Literary data and practice of the specialized orphanage work indicate that the insufficient development of theoretical and practical aspects and practical approaches to setting work on the development of skills and abilities of self-service in children with a severe degree of mental retardation in these institutions significantly complicates the effective organization and conduct of this work. As a result, these children are constantly under excessive care from educators, nannies and teachers of a specialized orphanage, and these children practically do not have the skills and abilities of self-service in various activities. Therefore, the development and substantiation of theoretical and practical approaches to constructing work on the formation and development of self-service in children with a severe degree of mental retardation in a specialized orphanage will become the basis for an effective solution to this problem. The foregoing determines the relevance of the problem under consideration, its theoretical and practical significance. Insufficient development of many issues of this problem further aggravates it. The article presents the main approaches to the construction of work on the formation and development of self-service in children with a severe degree of mental retardation in a specialized orphanage.